Women in the sky : gender and labor in the making of modern Korea - Nam, Hwasook, 1959- (ILR Press, an imprint of Cornell University Press, 2021)
"This book examines Korean women factory workers' century-long activism from the 1920s to the present in broad historical context with a focus on gender politics in the labor movement and in the larger society"--